ACTIVATED POLYPROPYLENE MEMBRANES WITH ION-EXCHANGE POLYMERS TO TRANSPORT CHROMIUM IONS IN WATER - Yesid Tapiero; Bernabe L Rivas; Julio Sanchez (Journal of the Chilean Chemical Society, 2019)
Polypropylene (PP) membranes were modified by in situ radical-polymerizations of functional monomers forming networks inside the pores. The main experimental conditions studied include the functional monomer concentration and crosslinking concentration.The modified membranes were characterized by scanning electron microscopy, charge density properties, and Donnan dialysis for chromium ion transport. The experimental data of the transport of Cr(III) and Cr(VI) ions were fitted to mathematical models (a polynomial fit as the first step and then the change in the concentration rates of both phases). The 4-order polynomial equation for the Cr(III) ions and the 7-order polynomial equation for the Cr(VI) ions provide better fits to the data and aid in predicting the chromium concentration values for any time.